BILATERAL PEACE AND SECURITY: ROLE OF CHINESE ECONOMIC ENGAGEMENT IN CENTRAL ASIA - Bakhshaliev, Elmin; Khan, Dr. Hameed (The journal of contemporary issues in business and government, 2023)
The relationship between peace and economic interdependence is one of the oldest debates in the field of international relations. Liberals contend that growing economic interconnectedness will reduce the likelihood of war since neither side will be willing to pay the opportunity costs of a military confrontation. Realists like Waltz argued that while interdependence helps to promote peace in some ways, it also increases the likelihood of conflicts. Dale Copeland used viewpoints from both sides to make the case that, depending on expectations for the future trading environment, interdependence might result in peace. The subject of whether economic interdependence leads to peace needs to be re-examined in light of the current trade war. Furthermore, it makes the case that the Chinese optimistic expectations for the state of trade in the future are what led to increase in peace in the region.